The Sun, 27 April 2009 (Star Publications (Malaysia) Berhad, 2009)
The Health Ministry is taking immediate action to keep out the lethal Mexican flu strain which has killed scores of people, health director-general Tan Sri Dr Mohd Ismail Merican said yesterday.